2011
DOI: 10.1017/s1368980011001170
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of a telephone-based parental intervention to increase fruit and vegetable consumption in 3–5-year-old children

Abstract: Objective: To examine the potential efficacy of a brief telephone-based parental intervention in increasing fruit and vegetable consumption in children aged 3-5 years and to examine the feasibility of intervention delivery and acceptability to parents. Design: A pre-post study design with no comparison group. Telephone surveys were conducted approximately 1 week before and following intervention delivery. Setting: Participants were recruited through pre-schools in the Hunter region, New South Wales, Australia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…As such, we recently conducted a pre-post pilot trial and reported a significant postintervention increase in preschoolers’ fruit and vegetable consumption immediately after a 4-contact, telephone-based intervention (20). On the basis of the pilot findings and the broader telephone and health behavior literature (19), we sought to test the longer-term efficacy of the intervention in an appropriately powered randomized controlled trial.…”
Section: Introductionmentioning
confidence: 99%
“…As such, we recently conducted a pre-post pilot trial and reported a significant postintervention increase in preschoolers’ fruit and vegetable consumption immediately after a 4-contact, telephone-based intervention (20). On the basis of the pilot findings and the broader telephone and health behavior literature (19), we sought to test the longer-term efficacy of the intervention in an appropriately powered randomized controlled trial.…”
Section: Introductionmentioning
confidence: 99%
“…The average number of days between intervention telephone sessions in our pilot study (n = 14) was double the rate reported in the general pediatric population (n = 7) 34 . Considerably fewer parents completed the intervention within the 4‐week proposed schedule (7/16, 44%) compared with parents in the general pediatric population aged 2‐5 years (34/34, 100%) 34 . Unlike “Healthy Habits,” most of the young survivors whose parents participated in Reboot were of primary school age (19/22) 34,35 .…”
Section: Discussionmentioning
confidence: 49%
“…We found that parents frequently rescheduled intervention sessions, suggesting that the weekly intervention schedule may be burdensome for families of young survivors. The average number of days between intervention telephone sessions in our pilot study (n = 14) was double the rate reported in the general pediatric population (n = 7) 34 . Considerably fewer parents completed the intervention within the 4‐week proposed schedule (7/16, 44%) compared with parents in the general pediatric population aged 2‐5 years (34/34, 100%) 34 .…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations